2002
DOI: 10.1152/ajpgi.00304.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increased cytochromeP-450 2E1 expression sensitizes hepatocytes to c-Jun-mediated cell death from TNF-α

Abstract: Liu, Hailing, Brett E. Jones, Cynthia Bradham, and Mark J. Czaja. Increased cytochrome P-450 2E1 expression sensitizes hepatocytes to c-Jun-mediated cell death from TNF-␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…144 Moreover, studies in other cell types using inhibitors of the JNK pathway also revealed a proapoptotic function of the JNK pathway in TNF-induced cell death. [262][263][264][265][266][267][268] The different roles of JNK in TNF-induced apoptosis could be partly related to celltype-specific effects, but may also mirror that TNF engages JNK by more than one pathway. Indeed, especially under apoptotic conditions, TNF activates JNK, but also p38, with biphasic kinetics.…”
Section: Molecular Mechanisms Of Tnf-induced Cell Deathmentioning
confidence: 99%
“…144 Moreover, studies in other cell types using inhibitors of the JNK pathway also revealed a proapoptotic function of the JNK pathway in TNF-induced cell death. [262][263][264][265][266][267][268] The different roles of JNK in TNF-induced apoptosis could be partly related to celltype-specific effects, but may also mirror that TNF engages JNK by more than one pathway. Indeed, especially under apoptotic conditions, TNF activates JNK, but also p38, with biphasic kinetics.…”
Section: Molecular Mechanisms Of Tnf-induced Cell Deathmentioning
confidence: 99%
“…The ethanol sensitization of TNFα toxicity in E47 cells and hepatocytes from chronic ethanol fed rats also depended on P38 MAPK signaling since SB203580, a P38 MAPK inhibitor, prevented this enhanced toxicity (172). In a RALA hepatocyte cell line model, Czaja and collaborators showed that hepatocytes with increased expression of CYP2E1 were sensitized to TNFα mediated cell death (211). Toxicity was a mixture of necrosis and apoptosis, was associated with prolonged activation of JNK and phosphorylation of c-Jun, and could be prevented by a dominant negative c-Jun construct (211).…”
Section: Lps/tnfα-cyp2e1 Interactionsmentioning
confidence: 99%
“…In a RALA hepatocyte cell line model, Czaja and collaborators showed that hepatocytes with increased expression of CYP2E1 were sensitized to TNFα mediated cell death (211). Toxicity was a mixture of necrosis and apoptosis, was associated with prolonged activation of JNK and phosphorylation of c-Jun, and could be prevented by a dominant negative c-Jun construct (211). These results suggest that increased oxidant stress from CYP2E1 may sensitize isolated hepatocytes to TNFα-induced toxicity.…”
Section: Lps/tnfα-cyp2e1 Interactionsmentioning
confidence: 99%
“…studies have demonstrated that CYP2E1 overexpression causes an activation of JNK mitogen-activated protein kinase (45). JNK is known to phosphorylate inhibitory IRS serine residues in other cell types and in nonhepatic and hepatic tissues (14,20).…”
Section: Decreased Insulin Signaling In S-cyp Cells Is Partially Revementioning
confidence: 99%